Flagging Determinants for Indian Outbound M&A - Kapil, Sheeba; Dhingra, Puneet Kaur (International Journal of Economics and Financial Issues, 2021)
Indian enterprises have succeeded in climbing the ladder of outward M&A transactions and out performing everyone’s expectations post 1990s. This paper aims to recalibrate the empirical literature of India’s outbound M&A by considering the impact of host market size, appreciation in home currency, India’s trade openness and liberalization policies. This study attempts to examine the impact of the host market size, home international reserves and trade openness along with home currency appreciation on the volume of the outbound M&A by Indian firms, using augmented autoregressive distributed lag (augmented ARDL) bounds testing approach. Findings reveal that appreciation of Indian rupee and liberal norms towards trade, i.e. import and export both will inevitably benefit or push the Indian firms to acquire foreign firms overseas, in the short term as well as over the long term. This paper makes an effort to identify and describe the significant factors influencing the outbound M&A deals by Indian firms in the recent years, which were previously proved relevant for group of emerging economies at large. Keywords: Outbound M&A; India, OFDI, Determinants JEL Classiï¬cations: F21, F23, P45, G34 DOI: https://doi.org/10.32479/ijefi.11715